Introduction to the First Issue of 2025 - Gromova, Elizaveta; Brantes Ferreira, Daniel (International Journal of Law in Changing World, 2025)
In Memoriam of Alexander Grigorievich Kolchedantsev, March 11, 1946 - April 2, 2025.